2018
DOI: 10.1016/j.psyneuen.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of childhood trauma on cortisol levels in suicide attempters and ideators

Abstract: These results indicate that childhood trauma is associated with blunted HPA axis activity in vulnerable populations in adulthood. The challenge for researchers is to elucidate the precise causal mechanisms linking trauma, cortisol and suicide risk and to investigate whether the effects of childhood trauma on cortisol levels are amendable to psychological intervention.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 50 publications
4
48
1
2
Order By: Relevance
“…Although much of this research has been conducted in the United States [ 30 ] research conducted in European countries echoes these findings and has highlighted that as exposure to ACEs increases, this negatively impacts upon mental wellbeing [ 20 ] and is associated with increased risk of suicidal ideation [ 31 ]. Additionally, early life trauma is also associated with a blunted stress response among adults with a suicidal history [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although much of this research has been conducted in the United States [ 30 ] research conducted in European countries echoes these findings and has highlighted that as exposure to ACEs increases, this negatively impacts upon mental wellbeing [ 20 ] and is associated with increased risk of suicidal ideation [ 31 ]. Additionally, early life trauma is also associated with a blunted stress response among adults with a suicidal history [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The review also found that PTSD is rarely mentioned in the literature on suicide, and vice versa; risk of suicide is rarely mentioned in the literature related to trauma [34]. More recent research has indicated a strong link between childhood trauma and an increased risk of suicide [35,36]. Historically such patients have been routinely excluded from PTSD studies as they are perceived as too risky [37], adding to the myth that suicidal patients are not safe to be treated [38].…”
Section: Introductionmentioning
confidence: 99%
“…3 Some epidemiologic research has suggested that CS is an independent risk factor for the development of vascular diseases and increases the morbidity and mortality of patients with coronary artery disease. 4 CS is a nonspecific reaction to long-term repeated physical irritants (e.g., acute cardiovascular reaction to hypothalamic-pituitary-adrenal axis activation) 5,6 and psychological irritants (e.g., emotional responses). Additionally, ample evidence has shown that unpredictable mild CS can lead to depression, 7,8 and both the risk of cerebrovascular disease and higher fatality rates have been demonstrated by numerous researchers.…”
Section: Introductionmentioning
confidence: 99%